Restricted access-activated carbon clothes-based lead extraction from human serum: skipping the sample preparation step for biological media. Issue 11 (1st September 2016) - Ullah, Naeem; Shah, Faheem; Khan, Rafaqat Ali; Ateeq, Muhammad; Muhammad, Haji; Khan, Abdur Rahman
ABSTRACT: In this study, a new microextraction technique has been proposed which has the capability to extract lead (Pb) from human blood serum. Pb was directly extracted without any pretreatment step, whereas all the serum proteins were excluded. Initially, the surface of activated carbon cloths was decorated with bovine serum albumin using glutaraldehyde as cross-linker to prepare restricted-access-activated carbon cloths (RACCs). RACCs were then fixed in a filter holder to form a sorbent cartridge fixed at the tip of a syringe system coupled with electrothermal atomic absorption spectrometry. Experimental parameters that could possibly influence the extraction procedure were optimised. The limits of detection and quantification obtained were 1.9 and 6.3 μg L −1, respectively. Pb recoveries in fortified human serum samples were found in the range of 92.2–103.9%. The procedure was effectively used for Pb extraction in real samples devoid of any pretreatment step.